A Fractional Supervision Game Model of Multiple Stakeholders and Numerical Simulation. (13th April 2017) - Lu, Rongwu; Wang, Xinhua; Li, Dan
Abstract : Considering the popular use of a certain kind of supervision management problem in many fields, we firstly build an ordinary supervision game model of multiple stakeholders. Secondly, a fractional supervision game model is set up and solved based on the theory of fractional calculus and a predictor-corrector numerical approach. Thirdly, the methods of phase diagram and time series graph were applied to simulate and analyse the dynamic process of the fractional order game model. Results of numerical solutions are given to illustrate our conclusions and referred to the practice.